WORKING WITH HISTORICITY: TRACING SHIFTS IN CONTRACEPTIVE USE IN THE ACTIVITY SYSTEM OF SEX OVER TIME - van der Riet, Mary (PINS-Psychology in Society, 2025)
Sexual activity, sexuality and responses to HIV and AIDS in a rural context in South Africa were studied using a cultural-historical activity theory framework. Activity theory directs the focus onto activity and emphasises the importance of an historical perspective for understanding current preventative practices. Qualitative data were generated from interviews and focus groups with 45 male and female participants between 10 and 71 years of age. An activity system analysis illustrated critical historical changes in a mediational artefact (the form of contraception) in sexual activity. The shift from intercrural sex to the use of the injectable contraceptive set up particular conditions for condom use in response to HIV and AIDS.